Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/mlr.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in False-positive Mammogram Rates

Abstract: Background Mammography screening reduces breast cancer mortality, but false-positive tests are common. Few studies have assessed racial differences in false-positive rates. Objectives We compared false-positive mammography rates for black and white women, and the effect of patient and facility characteristics on false-positives. Research Design and Subjects Prospective cohort study. From a sample of the American College of Radiology Imaging Network (ACRIN) Digital Mammographic Imaging Screening Trial (DMIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…7,18 Mammographic accuracy, for example, has been shown to vary greatly based on institution and radiologist, with poorer performance at facilities that treat predominantly minority and low-income women. 18 Facilities that serve mostly racial/ethnic minority groups may have a history of chronic underinvestment, as NYC neighborhoods differ drastically in insurance coverage rates, income level, breast cancer rates. 19 Structural racism in and outside of healthcare centers negatively impact racial and ethnic minorities and are associated with worse healthcare access and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,18 Mammographic accuracy, for example, has been shown to vary greatly based on institution and radiologist, with poorer performance at facilities that treat predominantly minority and low-income women. 18 Facilities that serve mostly racial/ethnic minority groups may have a history of chronic underinvestment, as NYC neighborhoods differ drastically in insurance coverage rates, income level, breast cancer rates. 19 Structural racism in and outside of healthcare centers negatively impact racial and ethnic minorities and are associated with worse healthcare access and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of prior images is associated with higher false positive rates. 3,18 This issue may be more common among populations with less access to care. Availability of prior comparison studies have been shown to reduce false positive recalls for all breast imaging modalities, decreasing from 20.9% in first screening ultrasound to 10.7% in the second and third year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on current practices, women are assumed to be navigated until they complete care (e.g., diagnostic follow-up; treatment). For breast cancer, we will use data from published literature for AAs' prevalence of breast cancer risk factors [90,91], breast cancer transition probabilities [92], rates of false-positives and false-negatives [[92], [93], [94], [95]], linkages between screening and stage at diagnosis [49,96,97], NCI's Surveillance Epidemiology and Ends Results (SEER) data for AAs' cancer incidence, stage at diagnosis, and survival data [98].…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Although the overall incidence of breast cancer is lower among African American (AA) women compared with Caucasian women, AA breast cancer patients of all ages are more likely to have advanced disease at diagnosis, an increased risk of recurrence and a poorer prognosis ( 2 6 ). Racial disparities in breast cancer mortality in the US persist, with AA breast cancer patients experiencing higher mortality rates compared with their Caucasian counterparts ( 7 9 ). Recent data from the 50 largest US cities confirms the trend of increasing racial disparities ( 8 ).…”
Section: Introductionmentioning
confidence: 99%